Good Corporate Governance, Corporate Social Responsibility and Firm Performance: Study on Companies Listed in Indonesia Stock Exchange - Sutrisno, Tamarinda Filia Dona dan (Account and Financial Management Journal, 2022)
One of the obligations of a companies that go public is the disclosure of information and the company’s concern for the community as indicated by the company’s obligation to implement good corporate governance (GCG) and corporate social responsibility (CSR). This study aims to examine the effect of corporate governance mechanisms and corporate social responsibility on firm performance. Firm performance is measured by return on equity (ROE), while the corporate governance mechanism is proxied by institutional ownership, independent board of commissioner, audit committee, while corporate social responsibility is measured by the number of CSR items disclosed. This study uses firm size as a control variable. The population in this study are companies listed on the Indonesian Stock Exchange (IDX). While the samples taken were 50 companies with an observation period of three years (2019 – 2020). To test the hypothesis, using multiple regression analysis with a significance level of 0.05. The results showed that institutional ownership, independent board of commissioners, audit committee and corporate social responsibility had no effect on firm performance.